The Value of Creative Character of Guci Dance Through The Extracurricular Art of Dance - Ferawati, Yusnita; Hartono, Hartono; Triyanto, Triyanto (Universitas Negeri Semarang, 2020)
Guci dance is one of the dance creations from the Guci area in Tegal Regency which had a characteristic in its variety of movements and it was used as a material for the extracurricular art of dance. This study aims to provide an overview of the value of the creative character of the Guci Dance, which was given through the extracurricular activities learning of dance. The study was conducted by using a qualitative analysis research method with the research location at SMP Negeri 2 Bumijawa in Tegal Regency. The instruments and data collection techniques used observation, interviews, and document study. The data validity technique used data triangulation technique. Meanwhile, data analysis and processing techniques were carried out by collecting, reducing, clarifying and verifying data. The results of the cultivation of creative character values through the extracurricular activities learning art of dance focused on 5 aspects, namely thinking in all directions, changing perspectives, generating ideas, stimulating backgrounds and skills in many ways.